Disaster planning and preparedness : The case of Protea-South, Johannesburg - Tebid, Theophilus Nji (My University, 2008)
Despite increasing philosophical knowledge of disaster planning and preparedness, disasters still remain a challenge in many communities. As a result, communities, environment and economies remain considerably vulnerable and at the risk of disaster destruction hence, sustainable development is undermined. The purpose of this study is to review and assess the state of community readiness in order to prevent and mitigate common hazards in the City of Johannesburg, especially in previously disadvantaged communities such as Protea-South. A survey and interviews was conducted with the local community members. Results show that, this community like many others, is at high risk, due to their living circumstances. e.g. the presence of densely built shacks on a flood plain; poor hygiene and sanitation, pollution, poverty etc. There is therefore a need for a paradigm shift by institutions from emergency response and the provision of hard infrastructure to disaster prevention, preparedness and soft infrastructure provision by means of an approach encompassing collaborative planning.
Keywords: disaster; shared interest; preparedness; collaborative planning; vulnerability; risk; good governance